InnovaHub networks for agrifood innovation and scaling: Communication strategy and outreach activities - Arce Gómez, Daniela; Alarcón, Francisco; Lizarazo, Miguel; Borrayo, Andrea; Jiménez, Daniel; Van Loon, Jelle; Martínez, Jesús David (2024)
This communication strategy focuses on engaging stakeholders by highlighting the milestones and outcomes achieved through the AgriLAC Resiliente regional initiative, with a particular emphasis on the development and operation of Innovahubs across the region. This report provides an overview of the strategy and details the diverse communication and outreach materials produced in 2024. In the context of AgriLAC Resiliente, effectively communicating field-level actions and accomplishments led by the technical implementation team is crucial. The objective is to spotlight the activities facilitated through Innovahubs and their local partners, showcasing the dedication and collaboration of stakeholders at a regional scale. By fostering a sense of community and shared purpose, these efforts build ownership and encourage active participation within the AgriLAC initiative. The communication and outreach activities underscore the importance of collective action and celebrate the contributions of Innovahub actors to advancing sustainable and resilient agricultural practices.